Characterization of a core fragment of the rhesus monkey TRIM5α protein - Kar, Alak K (BioMed Central, 2011)
BACKGROUND: Like all tripartite motif (TRIM) proteins, the retroviral restriction factor TRIM5α consists of RING, B-box 2 and coiled-coil domains, with a C-terminal B30.2(SPRY) domain. Although structures have been determined for some individual TRIM domains, the structure of an intact TRIM protein is unknown. RESULTS: Here, we express and characterize a protease-resistant 29-kD core fragment containing the B-box 2, coiled coil and adjacent linker (L2) region of TRIM5α. This BCCL2 protein formed dimers and higher-order oligomers in solution. Approximately 40% of the BCCL2 secondary structure consisted of alpha helices. Partial loss of alpha-helical content and dissociation of dimers occurred at 42°C, with the residual alpha helices remaining stable up to 80°C. CONCLUSIONS: These results indicate that the B-box 2, coiled-coil and linker 2 regions of TRIM5α form a core dimerization motif that exhibits a high level of alpha-helical content.